An In Situ Grazing Incidence X‐Ray Scattering Study of Block Copolymer Thin Films During Solvent Vapor Annealing. (27th November 2013) - Gu, Xiaodan; Gunkel, Ilja; Hexemer, Alexander; Gu, Weiyin; Russell, Thomas P.
<x xml:space="preserve">Abstract</x> In situ grazing‐incidence small‐angle X‐ray scattering experiments on thin films of block copolymers during annealing in neutral solvent vapors are reported. By removing the solvent in a controlled manner, the period of the microphase separated morphology is found to increase with increasing block copolymer concentration in a power law manner with an exponent ∼ 2/3. By venting the systems at different rates during the solvent removal process, kinetically arresting the system, the period of the microphase separated morphology in the dried film can be varied. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>